AN EXAMPLE OF THE CLINICAL CASE OF ISOLATED DIASTOLIC ARTERIAL HYPER- AND HYPOTENSION - Strikhar, V. A.; Fomich, A. N.; Yabluchansky, N. I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
An example of the clinical case demonstrates a significance of the correct diagnosis and treatment of isolated diastolic arterial hyper-and hypotension in patient with sympathetic distress and atherosclerosis. Research methods comprised lipid profile, heart rate variability, blood pressure monitoring and Holter ECG. The crucial role in the treatment of the patient belonged to biofeedback and medical therapy with atorvastatin and cinnarizine.